1 - Les Tribulations de la Sociologie gabonaise: science des problèmes sociaux ou science des faits construits? - Jean Ferdinand Mbah, (African Sociological Review, 2001)
Economies, Law and History as disciplines are well known and estab lished in Gabon. This is not the case with Sociology, which even though introduced in the Faculty of Letters and Social Sciences since 1970, is still not well known due to the fact that it tends rather to salve practical problems, especially those related ta development. lt is also not well appreciated because it is always seen as rooted in and brought to the fore by social dynamics and group strategies. ln a case where the practice of sociological research is insufficiently convincing about the use of Sociol ogy, a certain tendency will arise, which, bit by bit, will transform the sociologist into an expert. This article sets out ta present a picture of the sociologist and of sociology in Gabon. ln so doing, it does not only pres ent the pioneers of Sociology in Gabon and where they operate from, but also the difficulties of the domestication of Sociology, which is partly linked to its orientation that has tended to minimise its own existence and institutionalisation, and ta dwell instead on society and its hierarchies and dynamisms.